Passive cooling technologies for building envelope - Kong, Maureen Yan Hui (2016)
Over the years, energy demand has increased significantly with the increase in the world population. According to Energy Market Authority, 50% of the total energy consumption in a building in Singapore is used in air-conditioning and mechanical ventilation (ACMV) system. An effective way to conserve energy would be to reduce energy usage on such instruments by pushing for passive cooling technologies. Roof is where most heat transfer takes place through the opaque envelope of a building. Studies have shown that 50 to 60 percent of the total thermal load in the building comes from heat gain through the roof. Hence, reducing heat gain from the roof would be an effective way to reduce energy consumption in a building substantially. Presently, the common practices are to use cool roof, green roof, insulation roof and phase change material (PCM) roof. The results in Singapore had shown that cool roof gave the best result for energy saving of 5.3%, followed by insulation 2.1%, green roof of 0.6% and lastly phase change material, giving the lowest result of 0.1%. Based on our studies, cool roof works best in hot climates such as Abu Dhabi with an energy consumption reduction of 5.3% to 10.4%. Insulation works best in cold climates such as San Francisco with an energy consumption reduction of 11.3% to 16.5%.